El parlamento de Juan II ante las cortes generales de Monzón (1469). Una pequeña crónica autobiográfica en lengua castellanoaragonesa. - GUIXERAS, DAVID; VELA, AGUSTÍN RUBIO (Scripta, 2016)
This article contains the critical edition and study (history, form and language) of John II of Aragon's opening speech, which took place at the general court in Monzón on 13th November 1469. At the height of Catalan Civil War, the rebels had offered the crown to Renato of Anjou. However, his son's arrival, the duke of Lorena, from France with a powerful army forced the king to ask for beneits in order to face up to the grave situation. In this discourse, one of the few remaining samples of the late Aragonese language, the king produced an autobiographical account of his reign with an undeniable manichaen guidance.